Integrity Challenges of Audio-Visual Journalism in the Era of Artificial Intelligence - Abdul Syukur; Faisal Utama; Edison Bonar Tua Hutapea (Civilization Research: Journal of Islamic Studies, 2026)
Maintaining integrity and professional morality amid the secondary disruption of the broadcasting media industry due to Artificial Intelligence (AI) integration has become crucial and vital. AI carries the risk of bias and hallucination, while regulations are not yet fully capable of anticipating this "AI tsunami." This research is highly important as a source of input and consideration for journalism stakeholders to protect the integrity of the newsroom, ensuring it remains sterile from the negative impacts of AI. The primary objective of this study is to analyze the multiplier effect of artificial intelligence (AI) on press integrity in Indonesia and to evaluate the effectiveness of existing domestic legal instruments. Beyond the framework of domestic law, this discussion also attempts to examine the Islamic perspective on the AI "tsunami," which can be misused to generate hoaxes and misinformation. The methodology employed is descriptive and qualitative through a normative-legal approach, using a critical paradigm as the analytical tool. The methodological analysis reveals an asymmetrical misalignment between the evolutionary speed of generative technology and the scope of formal normative law, which triggers regulatory gaps that are vulnerable to exploitation for capital accumulation. The novelty of this research lies in the integration of the legal deconstruction of Press Council Regulation (Peraturan Dewan Pers) Number 1 of 2025 with an analysis of viewers' visual cognitive impact, using Ulric Neisser’s Cognitivism Theory, Elihu Katz’s Uses and Gratifications Theory, David Manning White’s Gatekeeping Theory, and the concept of Tabayyun in Islamic theology. The implications of this research emphasize the urgent need for operational policy reform in newsrooms that positions human journalists as absolute ethical quality controllers to safeguard the public sphere from the threat of machine-manufactured audiovisual disinformation.